2010
DOI: 10.1007/s00572-010-0343-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of twice-ambient carbon dioxide and nitrogen amendment on biomass, nutrient contents and carbon costs of Norway spruce seedlings as influenced by mycorrhization with Piloderma croceum and Tomentellopsis submollis

Abstract: Elevated tropospheric CO(2) concentrations may increase plant carbon fixation. In ectomycorrhizal trees, a considerable portion of the synthesized carbohydrates can be used to support the mutualistic fungal root partner which in turn can benefit the tree by increased nutrient supply. In this study, Norway spruce seedlings were inoculated with either Piloderma croceum (medium distance "fringe" exploration type) or Tomentellopsis submollis (medium distance "smooth" exploration type). We studied the impact of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
2
20
0
Order By: Relevance
“…Godbold et al 1997;Treseder 2004;Alberton et al 2005;Fransson et al 2005;Alberton and Kuyper 2009). However there are exceptions, for example Weigt et al (2011) found no increase or only a slight increase in EMM length using seedlings of Picea abies inoculated with Piloderma croceum and exposed to double or ambient CO 2 concentration alone or in combination with addition of ammonium nitrate solution. The effect of elevated CO 2 on EMM production has mostly been studied in laboratory grown seedlings.…”
Section: Effect Of Elevated Atmospheric Comentioning
confidence: 99%
See 1 more Smart Citation
“…Godbold et al 1997;Treseder 2004;Alberton et al 2005;Fransson et al 2005;Alberton and Kuyper 2009). However there are exceptions, for example Weigt et al (2011) found no increase or only a slight increase in EMM length using seedlings of Picea abies inoculated with Piloderma croceum and exposed to double or ambient CO 2 concentration alone or in combination with addition of ammonium nitrate solution. The effect of elevated CO 2 on EMM production has mostly been studied in laboratory grown seedlings.…”
Section: Effect Of Elevated Atmospheric Comentioning
confidence: 99%
“…So far one laboratory study has reported an increased proportion of mycorrhizas producing thick mantles and abundant rhizomorphs in response to elevated CO 2 (Godbold et al 1997), and only one of the few field studies showed that rhizomorph production was almost doubled by elevated CO 2 in deeper soil layers in a Pinus taeda forest (Pritchard et al 2008). The production of EMM varies greatly between different exploration types (Weigt et al 2011) and it seems reasonable to find increased abundance of high C demanding exploration types when C availability is increased by elevated CO 2 . Clearly further field studies on the effects of elevated CO 2 on mycelium production are needed.…”
Section: Effect Of Elevated Atmospheric Comentioning
confidence: 99%
“…The extraradical mycelia of ectomycorrhizal fungi enormously increase the space plant roots occupy for water and nutrient gain (Cairney and Burke 1986;Leake et al 2004;Read 1992;Smith and Read 2008), but the costs for ectomycorrhizae are substantial (Rygiewicz and Andersen 1994;Weigt et al 2011). Therefore, the exploration types raise two different issues in the functioning of the mutualistic symbiosis: (1) the benefit for the plant as expressed by the range of soil occupation by the mycelium to explore and exploit the soil and finally transport water and nutrients to the roots and (2) the costs for the tree which are mainly expressed by the carbohydrates that have to be invested by the tree to support its fungal partner (Weigt et al 2012).…”
Section: The Increase In Volume Of Exploited/explored Soil By Ectomycmentioning
confidence: 99%
“…It has been shown that rhizomorphs of the MDs-and the LD-ET differ in their capacities to transport phosphate (Kammerbauer et al 1989) indicating an important differential influence on tree growth. The EMM of ECM fungi enormously increase the space plant roots occupy for water and nutrient gain (Read 1992;Ekblad et al 1995;Cairney and Burke 1996;Smith and Read 2008), but the costs for ECM are substantial (Rygiewicz and Andersen 1994;Weigt et al 2010) Therefore, the ET comprises two different issues for function of the mutualistic symbiosis: (1) the benefit for the plant as expressed by the range of soil occupation by the mycelium to explore and exploit the soil and finally transport water and nutrients to the roots, and (2) the costs for the tree which are mainly expressed by the carbohydrates that have to be invested by the tree for support of its fungal partner. Space occupation and carbon costs are therefore crucial for function and the main focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The extension and intensity of space occupation by EMM influence the plant's carbohydrate sink and its supply of nutrients and water (Read 1992;Rygiewicz and Andersen 1994;Högberg and Högberg 2002;Wallander et al 2003;Leake et al 2004;Smith and Read 2008;Weigt et al 2010). Thus, the ecological importance of the EMM regarding resource capture (Kammerbauer et al 1989;Wallander 2000;Rosling and Rosenstock 2008) and carbon sink (Colpaert et al 1992;Finlay and Söderström 1992;Leake et al 2004;Weigt et al 2010) highlight the need for quantification, e.g. when assessing impacts of altered carbon allocation in relation to environmental conditions (Clemmensen et al 2006;Anderson and Cairney 2007;Parrent and Vilgalys 2007;Weigt et al 2010).…”
Section: Introductionmentioning
confidence: 99%